Interleukin-23 Blockers: Born to be First-line Biologic Agents in Inflammatory Bowel Disease? - Argollo, Marjorie C.; Allocca, Mariangela; Furfaro, Federica; Peyrin-Biroulet, Laurent; Danese, Silvio (Current Pharmaceutical Design, 2019)
Over the past decades, the advent of anti-TNF agents has dramatically changed the treatment algorithms for IBD. However, primarily and more importantly, secondary loss of response to anti-TNF agents, is often observed. Thus, new treatment options have been actively explored and some have already been incorporated in the current clinical practice. Among the class of anti-cytokine agents, the anti-IL12/IL23 monoclonal antibodies (mAbs) have been first presented, in clinical practice, by the anti-p40 mAb ustekinumab in Crohn’s disease (CD). More selective anti-IL23 agents (anti-p19) have shown efficacy and are being further developed, in contrast to agents inhibiting IL-17 downstream, which have failed in IBD clinical trials despite their clear efficacy in psoriasis.
Keywords: ulcerative colitis